Comparison of assessments of fitness to drive for people with dementia - Vella, Kristina; Lincoln, Nadina (Taylor & Francis, 2014)
Cognitive tests are used to inform recommendations about the fitness to drive of people with dementia. The Rookwood Driving Battery (RDB) and Dementia Drivers' Screening Assessment (DDSA) are neuropsychological batteries designed to assist in this process. The aim was to assess the concordance between the classifications (pass/fail) of the RDB and DDSA in individuals with dementia, and to compare any discordant classifications against on-road driving ability. Participants were identified by community mental health teams and psychiatrists. Twenty four participants were recruited. The mean age was 74.1 (SD 8.9) years and 18 (75%) were men. Each participant was assessed on the RDB and DDSA in an order determined by random allocation. Those with discrepant results also had an on-road assessment. The agreement between the tests was 54% using a cut-off of > 6 on the RDB, and 75% using the cut-off to > 10 on the RDB. Three participants with discrepant results agreed to be assessed on the road and all were found to be safe to drive. The findings suggested that there was poor concurrent validity between the RDB and DDSA. This raises questions about the choice of assessments in making clinical recommendations about fitness to drive in people with dementia.